Phamartes coronatus gen. nov. sp. nov. a new genus and species of stick insect from Bach Ma National Park, central Vietnam (Phasmida, Diapheromeridae, Necrosciinae) - Bresseel, Joachim; Constant, Jerome (Zootaxa, 2013)
A new genus and species of stick insect Phamartes coronatus gen. nov. sp. nov. from Bach Ma National Park, central Vietnam is described and illustrated from both sexes and the egg. The genus is most closely related to Oxyartes Stål, 1875, but easily distinguishable by the presence of fully developed alae, the head armature and the split and asymmetrical anal segment, a character previously unknown in Necrosciinae.